Air Filtration: A Controlled Design of Ripple‐Like Polyamide‐6 Nanofiber/Nets Membrane for High‐Efficiency Air Filter (Small 10/2017). Issue 10 (8th March 2017) - Zhang, Shichao; Liu, Hui; Zuo, Fenglei; Yin, Xia; Yu, Jianyong; Ding, Bin
Abstract : A ripple‐like polyamide‐6 nanofiber/nets membrane filter composed of twodimensional nanonets (≈20 nm) and a scaffold framework is fabricated by Bin Ding and co‐workers in article number 1603151, by combining an electrospinning/netting technique with the receiving substrate design. By virtue of its small pore size and stable cavity structure, the filter can filtrate ultrafine airborne particles with a high removal efficiency of 99.996%, low air resistance of 95 Pa, using a physical sieving manner.